Fatigue and conformist traits in the performance of young swimmers Fatiga y rasgo conformista en el rendimiento de jovenes nadadores - Nuñez Espinosa, Cristian Andrés; Herrera-Valenzuela, T.; Valdés-Badilla, P.; Estrada Goic, Claudia Andrea (My University, 2021)
Objective: Determine the relationship between the fatigue of adolescent swimmers in high-level competitions during two continuous periods of maximum performance and the degree that swimmers conform to norms during these periods. Methods: We evaluated the conformist trait and three areas of fatigue in two consecutive competitive periods, in 25 young elite swimmers. The measures were evaluated before (_B) and after (_A) of pre (t1; t3) and pos (t2; t4) competition in each period. Millon Adolescent Clinical Inventory was applied for identifies the more adherens (AD; n=12) or detached from the norm (DN; n=13) conformist traits. Wingate test, Heart rate variability (RMSSD; SDNN), WISC-V, and Stroop test were evaluated. Results: DN group present lower fatigue in t1 but an increase in t2, t3, and t4. AN present higher RMSSD_B and SDNN_B in t1. In t3, the mental fatigue of DN was correlated negatively with RMSSD_B; SDNN_B. Both groups had more SDNN_B than SDNN_A in t4. Conclusions: Physical fatigue was an important conditiong in both groups, however, the DN group may be more sensitive to physiological and mental fatigue directly affecting the sports performance.
Keywords: heart rate variability; personality trait; sports performance; state of fatigue